2011
DOI: 10.1177/1545968311403494
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Biomechanical Model to Measure Muscle Tone in Spastic Muscles

Abstract: The results suggest that the model allows valid measurement of spasticity in the upper extremity of chronic stroke patients and that it can be used to separate the neural component induced by the stretch reflex from resistance caused by altered muscle properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 223 publications
(355 reference statements)
6
150
1
5
Order By: Relevance
“…One of the difficulties in the clinical assessment of muscle tone is that abnormal muscle tone is often considerably more complex and nonlinear than healthy muscle tone. For example, spasticity in poststroke patients is associated with exaggerated reflex response, and it is proportional to the speed of passive motion (Lindberg et al 2011;Pisano et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One of the difficulties in the clinical assessment of muscle tone is that abnormal muscle tone is often considerably more complex and nonlinear than healthy muscle tone. For example, spasticity in poststroke patients is associated with exaggerated reflex response, and it is proportional to the speed of passive motion (Lindberg et al 2011;Pisano et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent studies have indicated that Neuroflexor is a reliable measurement tool with high test-retest and interrater reliability, 12 and its sensitivity is good enough to measure changes in spasticity during CP treatment. 13 The purpose of this case series is to describe the quantitative changes in wrist muscle spasticity in children with CP after 1 SM and after a 2-week course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos estímulos externos, que são frequentemente responsáveis por mudanças de tônus, incluem-se: temperatura ambiental, ruídos, estímulos nocivos da pele devido a roupas apertadas e posições das partes do corpo (BLACKBURN, VLIET, MOCHETT, 2002;MENSE;MASI, 2010;UNPHRED, 1994). No entanto, existe também uma resistência de origem não neural causada por inércia, elasticidade e viscosidade da parte do corpo que é movida, mostrando que as propriedades do músculo são alteradas após a espasticidade (LINDBERG et al, 2011).…”
Section: Espasticidade E Alteração De Forçaunclassified
“…Os autores mostraram que a matriz extracelular no músculo espástico ocupa mais espaço no feixe do músculo e que a matriz extracelular é mais desorganizada. Assim, sugere-se que a viscosidade é reduzida secundária a remodelação da matriz extracelular (isto é, desorganização de proteínas, tais como o colágeno), o que no AVE pode ser a explicação da diminuição da massa muscular (LINDBERG et al, 2011).…”
Section: Espasticidade E Alteração De Forçaunclassified
See 1 more Smart Citation